Families of children with special educational needs: perceptions of social support and parental well-being - Felizardo, Sara (2023)
Research on social support in families of children with Special Educational Needs (SEN) points its influence in parents’ health and well-being as well as in their involvement in the educational and therapeutic process. National and international laws assign parents a central role in assuring children’s educational interests. Promoting quality of life and well-being are key areas in educational and therapeutic contexts. The aim of this study is to: i) compare parents of children with and without SEN in social support and parental well-being (life satisfaction) and these variables in parents of children with different problems; ii) understand the relationship between social support and well-being; iii) analyze the effect of sociodemographic variables on social support and parental well-being. This is a non-experimental and cross-correlated study with a non-probabilistic and convenience sample of 152 parents of children with SEN and 149 without SEN. Of the 152 children, 53.9% (n=82) showed Intellectual Disabilities (ID), 24.3% (n=37) Motor Disabilities (MD) and 21.7% (n=33) Autism Spectrum Disorders (ASD). Data were collected in the central region of Portugal. Instruments: Social Support Questionnaire – short version, Life Satisfaction Scale; and a parental sociodemographic questionnaire. There are significant and positive correlations (r=0.539, p<.001) between social support and well-being (life satisfaction). Both parent groups have significant differences in well-being and in satisfaction with social support. In the SEN group, parents of children with ASD showed significantly higher values in social support than those with children with ID (p=.001) and MD (p=.004). A similar trend was observed in life satisfaction scale, but only with the ID group (p=.005). The results highlight the relationship between well-being/life satisfaction and social support and the need to invest in social support in SEN children’s families. Intervention programs should include ways to support family’s adaptation, empowering them to deal with these children giving them special attention. In the ecological/systemic and social support approaches, families are perceived as having skills, resources and needs, and the professionals should be, essentially, promoters, in a (co)constructed and dynamic process between family and technical expert, respecting family’s autonomy.